Dreamers’ evaluation of the emotional valence of their day-to-day dreams is indicative of some mood regulation function - Barbeau, Kheana; Turpin, Chloé; Lafrenière, Alexandre; Campbell, Emma; De Koninck, Joseph (Frontiers in Behavioral Neuroscience, 2022)
Dreams may contribute to psychological adaptation by aiding in mood regulation. This would be achieved through a desensitization process whereby negative events are replayed within the dream under lower conditions of negative emotionality. Evidence of this theory is supported by the tendency of dreamers to evaluate their emotions felt in their dreams more positively compared to an independent judge (i.e., positivity bias). Additionally, it has been observed that while dream emotions are typically more negative than pre-sleep emotions, morning emotions are more positive, suggesting that emotional regulation occurs overnight and may help improve mood in the morning. The present study aimed to examine the relationships between pre-sleep, dream, and morning mood and the potential desensitization function of remembered dreams as indicated by its effects on morning mood and stress. Methodology: Participants (N = 188; Mean age = 19.2, SD = 3.0) recorded their dreams (N = 345 dreams) and self-reported their stress and mood at bedtime, during their dream retrospectively, and upon waking. A judge also evaluated subjects’ dream mood. Subjects’ positivity bias was defined as the difference between the subjects and the judge’s evaluation of the positive emotions in the dream. Results: a MANOVA revealed that subjects perceived a higher level of positive emotions in their dreams compared to a judge. Multi-group path analysis revealed that some relationships between pre-sleep, dream, and morning emotions and stress differed in positive and negative dream nights. In both groups, the strongest predictors of morning mood and stress were pre-sleep mood and stress, respectively. The second strongest predictor of positive morning mood was subjects’ dream positivity bias. Conclusion: These results provide some support for the desensitization function of dreaming and its potential for mood regulation. They also highlight that pathways implicated in mood regulation may be distinct from stress regulation.